2022
DOI: 10.1186/s12889-022-13687-8
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the offer of COVID-19 vaccination to migrants and non-migrants in Norway: a cross sectional survey study

Abstract: Background Vaccination is key to reducing the spread and impacts of COVID-19 and other infectious diseases. Migrants, compared to majority populations, tend to have lower vaccination rates, as well as higher infection disease burdens. Previous studies have tried to understand these disparities based on factors such as misinformation, vaccine hesitancy or medical mistrust. However, the necessary precondition of receiving, or recognizing receipt, of an offer to get a vaccine must also be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
12
1
1
Order By: Relevance
“…This issue was manifested in the studies among refugee groups in Norway, where one large study from the country involved 1284 immigrant individuals in Oslo. The results revealed that people of migrant status had a lower likelihood of being offered to get vaccinated compared to native Norwegians [28] . This comes in spite of similar rates of COVID-19 vaccine hesitancy in people of migrant status and native citizens as showed in a recent study by Ebrahimi et al in the Nordic country [69] .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This issue was manifested in the studies among refugee groups in Norway, where one large study from the country involved 1284 immigrant individuals in Oslo. The results revealed that people of migrant status had a lower likelihood of being offered to get vaccinated compared to native Norwegians [28] . This comes in spite of similar rates of COVID-19 vaccine hesitancy in people of migrant status and native citizens as showed in a recent study by Ebrahimi et al in the Nordic country [69] .…”
Section: Discussionmentioning
confidence: 90%
“…Contributing factors of COVID-19 vaccine acceptance included origin of migrants [59] , [60] , gender [28] , [61] , [62] , [63] , [64] , [65] , [66] , [67] age [63] , [65] , [67] , being enrolled in school [66] and being educated [28] , [63] , [67] , marital status [63] , durations of residence [28] , [67] , having health insurance [66] , political mistrust [59] , [61] and mistrust in vaccinations [65] , [68] , perceived individuals’ physical health [60] , perceived risk of vaccination [69] , [70] , preference to maintain precaution measures, [71] , the belief that COVID-19 vaccines are not essential [71] , superiority of natural immunity [69] , fear of personal infection [59] , being worried about getting COVID-19 infection [72] , fear concerning significant others being infected by the virus [69] , trust in health officials’ dissemination of vaccine-related information [69] , lower logistical barriers and attitudes [15] , physicians’ recommendation, vaccine price, vaccine effectiveness and importance [70] , concerns regarding newness of the vaccines [71] , vaccine safety [62] , [65] , [68] and longer-term adverse effects [62] , and being a physician or advanced practice provider interacting directly with patients from refugee, immigrant, and migrant communities [65] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in Australia with a multinational refugee group (the majority of which were Arabic speakers), the vaccination rate was found to be 12% [ 25 ]. Similar to our country, a study in Norway determined that the probability of receiving the COVID-19 vaccine is one-third lower for immigrants than for non-immigrants [ 26 ]. There are other similar studies in which the probability of not being vaccinated in immigrants is 8–11 times higher than in the local population [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the lessons learnt from the COVID-19 pandemic research are still ongoing there is no doubt that inequities in health were unmasked. The research in the Nordic countries concurs with global research exposing migrants’ differential risks and differential clinical outcomes [52]. However, interpretations of the COVID-19-related migrant data and understanding the ‘causes of causes’ still need more research.…”
Section: A ‘Snapshot’ Of Migrant Health Research In the Nordic Countriesmentioning
confidence: 76%